Effect of sintering temperature and polyvinyl alcohol composition as binder on the formation of porous hydroxyapatite as bone graft using sponge replication method: A review - Baharudin Priwintoko; Rifky Ismail; Deni Fajar Fitriyana; Yusuf Subagyo; Athanasius Priharyoto Bayuseno (Mechanical Engineering for Society and Industry, 2023)
Hydroxyapatite (HA) is one of the inorganic components that has a role as a bone regeneration material. The potential for utilizing waste is one of the opportunities in HA commodities. Several waste materials that can be used as raw materials for HA include egg shells, beef bones, fish bones, limestone, and marine biota shells. Nowadays, the use of HA is not only limited to regeneration materials but also as a bone tissue scaffold. Porous HA is a form of HA that is in great demand today because it can be a good scaffold and regeneration material. One method that can be used to fabricate porous HA is the sponge replicated method. In its fabrication, the sponge replicated method is influenced by sintering temperature and binder composition. Polyvinyl alcohol (PVA) is a widely used binder because it can be evaporated without leaving traces and is biocompatible. This paper will examine the effect of sintering temperature and composition of PVA as a binder in pore HA fabrication. In particular, this paper compares the fabrication process with the characteristics of the resulting porous HA against commercial products and ISO 13379:2015 standards. According to the preliminary study, pore HA that conforms to the standard will have a good impact on the healing process of bone defects. The novelty of this research is to explore in depth related to the fabrication of HA pores using the sponge replicated method with sintering temperature parameters and the composition of PVA as a binder so that it is expected to be a literature for future researchers.